2015
DOI: 10.4103/0253-7613.165194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aqueous extract of Hibiscus sabdariffa on the renin-angiotensin-aldosterone system of Nigerians with mild to moderate essential hypertension: A comparative study with lisinopril

Abstract: Objectives:The present study investigated the effects of aqueous extract of Hibiscus sabdariffa (HS) on the three basic components of renin-angiotensin-aldosterone system: Plasma renin, serum angiotensin-converting enzyme (ACE), and plasma aldosterone (PA) in mild to moderate essential hypertensive Nigerians and compared with that of lisinopril, an ACE inhibitor.Materials and Methods:A double-blind controlled randomized clinical study was used. Seventy-eight newly diagnosed but untreated mild to moderate hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…This study included only studies that investigated sour tea effect by comparing with inactive control intervention. However, the question remains, “Is the blood pressure lowering effect of sour tea comparable to conventional anti‐hypertensive pharmacological agents?” A casual analysis was run on six studies (A Herrera‐Arellano et al, ; Armando Herrera‐Arellano et al, ; Nwachukwu, Aneke, Nwachukwu, et al, ; Nwachukwu, Aneke, Obika, & Nwachukwu, ; Seck et al, ; Soleimani, Akbari, Soleimani, Mousavi, & Tamadon, ), which were not included in this review (because of nonsuitability of their control groups) to answer this question. The forest plot showed that, in general, the effect of sour tea on blood pressure is remarkably lower than antihypertensive drugs (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…This study included only studies that investigated sour tea effect by comparing with inactive control intervention. However, the question remains, “Is the blood pressure lowering effect of sour tea comparable to conventional anti‐hypertensive pharmacological agents?” A casual analysis was run on six studies (A Herrera‐Arellano et al, ; Armando Herrera‐Arellano et al, ; Nwachukwu, Aneke, Nwachukwu, et al, ; Nwachukwu, Aneke, Obika, & Nwachukwu, ; Seck et al, ; Soleimani, Akbari, Soleimani, Mousavi, & Tamadon, ), which were not included in this review (because of nonsuitability of their control groups) to answer this question. The forest plot showed that, in general, the effect of sour tea on blood pressure is remarkably lower than antihypertensive drugs (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension has been positively correlated with thirst (Shailendra et al, 2011); it was reported to increase thirst perception (Stachenfeld, 2008), stimulate RAAS (Atlas, 2007) and alter sodium perception (Conlin et al, 1999). But H. sabdariffa consumption was reported to reduce plasma aldosterone level (Nwachukwu et al, 2015b) and exert antihypertensive action in humans (Herrea-Arellano et al, 2004;McKay et al, 2010). Decrease in plasma aldosterone was reported to cause natriuresis in normal humans (Gordon et al, 1997) and may be the mechanism responsible for the reduction in serum Na + with a consequent reduction in plasma osmolality and thus thirst perception.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind controlled randomized clinical study conducted with hypertensive to investigate effects of aqueous extract of HS on the RAAS, Placebo (150 mg/kg/day), lisinopril (10 mg once daily) and aqueous extract of HS (150 mg/kg/day) were given respectively for 4 weeks [43] . The results showed that HS reduced serum ACE and plasma aldosterone in patients with equal efficacy as lisinopril.…”
Section: Inhibition Of Ace Activitymentioning
confidence: 99%